Sn-containing high-strength heat-resistant magnesium alloy and preparation method thereof

By adding Sn to the magnesium alloy to form the Sn3Y5 phase and other strengthening phases, combined with high-frequency induction smelting and ultrasonic processing technology, a high-strength heat-resistant magnesium alloy with excellent high-temperature mechanical properties is prepared, solving the cost and The problem of ductility loss achieves both high temperature stability and lightweight.

CN119121020APending Publication Date: 2024-12-13CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411241286.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing high-strength magnesium alloys have rapid mechanical properties attenuated under high temperature environments, and the high content of rare earth elements leads to increased production costs and loss of ductility, making it difficult to control the amount of rare earths to obtain excellent heat resistance.

Method used

By adding Sn to the magnesium alloy, forming the Sn3Y5 phase, combining various strengthening phases such as LPSO and α-Mn, high-frequency induction smelting and ultrasonic treatment technology were used to prepare magnesium alloy ingots, followed by homogenization and extrusion treatment, and control The content of rare earth elements is below 10%, forming a multi-scale heat-resistant phase to improve high-temperature mechanical properties.

Benefits of technology

It achieves high temperature stability with a tensile strength of no less than 360MPa in the range of 250℃ to 300℃, with an elongation of more than 10%, and maintains the lightweight advantage of magnesium alloys, leading the vast majority of current high-strength heat-resistant magnesium alloys. And the process is simple and easy to be used in industrial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121020A_ABST
    Figure CN119121020A_ABST
Patent Text Reader

Abstract

The invention relates to a Sn-containing high-strength heat-resistant magnesium alloy and a preparation method thereof, and belongs to the technical field of magnesium alloy preparation. The magnesium alloy disclosed by the invention comprises the following components in percentage by weight: 6.3-9.7% of Y, 1.5-2.7% of Zn, less than or equal to 2.3% of Sn, 0.3-0.7% of Mn, less than or equal to 0.02% of inevitable impurities and the balance of Mg. The magnesium alloy with excellent high-temperature mechanical properties is successfully prepared by constructing a multi-scale heat-resistant phase and grain boundary segregation in the magnesium alloy. Alloy rare earth elements in the magnesium alloy do not exceed 10%, and the advantage of light weight of the magnesium alloy is guaranteed while the cost is controlled; according to the magnesium alloy, the tensile strength is not lower than 360 MPa when the environment temperature is increased to 300 DEG C from 250 DEG C, and the tensile strength is not reduced along with the increase of the environment temperature and is ahead of most of current high-strength heat-resistant magnesium alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy preparation, and relates to a Sn-containing high-strength heat-resistant magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium alloys have unique advantages in lightweighting, thanks to their low density and high specific strength. However, nuclear reactors and oil exploration often require components to work at higher ambient temperatures (200-300°C), which requires magnesium alloys to have excellent heat resistance. Adding other elements to magnesium alloys for alloying is the most common and effective method to strengthen magnesium alloys. Rare earth elements, as classic strengthening elements of magnesium alloys, can achieve excellent solid solution strengthening and precipitation strengthening effects in magnesium alloys, thereby improving room temperature and high temperature strength, which usually requires the addition of high rare earth content (>10wt%). The addition of high rare earth content will inevitably have a devastating impact on plasticity while achieving high strength. In recent years, researchers have been committed to developing high-strength Mg alloys without rare earths. Although relatively excellent results have been achieved, the mechanical properties rapidly decay in high temperature environments of 200-300°C. It can be seen that rare earth elements have irreplaceable characteristics in the development of high-strength and heat-resistant magnesium alloys. How to control the dosage of rare earth elements and obtain high-strength Mg alloys with no significant loss of ductility while controlling the preparation cost has become an urgent problem to be solved.

[0003] In recent years, the Mg-RE-Zn alloy has a unique LPSO structure, which can deform and kink to coordinate plastic strain, achieve short fiber reinforcement, and show satisfactory performance at room temperature and high temperature. Despite this, the LPSO phase will still dissolve at high temperature and lose the second phase strengthening effect. Researchers are committed to optimizing on this basis. RE / Zn atoms can be segregated on α-Mn, and α-Mn can promote the formation of lamellar LPSO phase, which also makes a positive contribution to the high temperature performance of magnesium alloys. In recent years, researchers have found that when Sn is added to the Mg-Y system, it will preferentially generate Sn3Y5 phase with lower Gibbs free energy rather than Mg2Sn phase. As a high temperature resistant precipitate, Sn3Y5 plays an important role in improving modulus and strength. At the same time, Sn3Y5 has extremely high thermal stability, which can effectively inhibit grain boundary sliding at high temperature and strengthen and toughen the alloy.

[0004] In view of this, magnesium alloys containing multiple strengthening phases such as LPSO, Sn3Y5 and α-Mn are expected to have excellent heat resistance, so it is necessary to conduct in-depth research. Summary of the invention

[0005] In view of this, one of the objects of the present invention is to provide a high-strength and heat-resistant magnesium alloy containing Sn; a second object of the present invention is to provide a method for preparing the high-strength and heat-resistant magnesium alloy containing Sn.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] 1. A high-strength and heat-resistant magnesium alloy containing Sn, wherein the magnesium alloy comprises 6.3-9.7% Y,

[0008] 1.5-2.7% Zn, 2.3% or less Sn, 0.3-0.7% Mn, 0.02% or less inevitable impurities, and the remainder Mg.

[0009] Preferably, the average grain size of the extruded magnesium alloy is not greater than 5 μm.

[0010] 2. A method for preparing the above magnesium alloy, the method comprising the following steps:

[0011] (1) Preparing a magnesium alloy ingot: placing pure Mg, Mg-30Y master alloy, Mg-4.1Mn master alloy, pure Zn particles, and pure Sn particles in a preheated high-frequency induction melting furnace for sequential melting, removing scum from the surface of the melt and cooling to 640-660°C, inserting a stirring head into the bottom of the melt and performing semi-solid stirring at a speed of 450-600 r / min for 30-50 s, increasing the speed to 750-850 r / min after the first stirring, and continuing to perform a second stirring at the middle of the liquid surface for 165-185 s, and after the two stirrings are completed, heating the stirred melt to 680-690°C, performing ultrasonic treatment at a power of 1600-1800 w for 220-280 s, and then removing the water cooling to obtain a magnesium alloy ingot;

[0012] (2) homogenizing the magnesium alloy ingot: heating the box-type heat treatment furnace to 510-520° C., placing the magnesium alloy ingot in a resistance furnace for 14-18 hours, and then air-cooling it to room temperature to obtain a homogenized magnesium alloy billet;

[0013] (3) Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: After the surface oxide layer of the homogenized magnesium alloy billet is polished, the billet is placed together with the extrusion die in a preheated box-type resistance furnace, and extruded in a horizontal extruder to obtain Sn-containing high-strength and heat-resistant magnesium alloy.

[0014] Preferably, in step (1), the preheating is specifically as follows: placing the cleaned stainless steel crucible in a high-frequency induction melting furnace and preheating it at 460-510°C for 20-30 minutes, while introducing a mixed protective gas formed by CO2 and SF6 with a volume percentage of 99:1.

[0015] Preferably, in step (1), the specific method for preparing the magnesium alloy ingot is:

[0016] A. Heat the high-frequency induction melting furnace to 720-750°C, add pure Mg to fully melt it, keep it warm and let it stand for 25-35 minutes to remove the slag on the surface of the melt;

[0017] B. Continue to heat the high-frequency induction melting furnace to 720-750° C., add Mg-30Y master alloy, and keep the master alloy warm for 25-35 minutes after it is completely melted, and remove scum on the surface of the melt;

[0018] C. After the high-frequency induction melting furnace is further heated to 720-750° C., Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the temperature is kept at room temperature for 25-35 minutes, and scum on the surface of the melt is also removed;

[0019] D. When the high-frequency induction melting furnace is further heated to 720-750° C., pure Zn particles are added to melt the melt and scum is removed from the surface of the melt;

[0020] E. When the high-frequency induction melting furnace is further heated to 720-750° C., pure Sn particles are added to melt the melt, and the scum on the surface of the Sn melt is removed after stirring the melt for 5-8 minutes;

[0021] F. After the impurities in the alloy melt are salvaged and the temperature is reduced to 640-660°C, use the stirring head to extend into the bottom of the melt for the first solid-state stirring, and then place the stirring head in the middle of the liquid surface for the second stirring;

[0022] G. After the two stirrings are completed, the stirred melt is heated to 680-690°C, ultrasonically treated at a power of 1600-1800W for 220-280s, and then the water cooling is removed to obtain a magnesium alloy ingot.

[0023] Further preferably, in the process of removing the scum on the surface of the melt, a colander coated with boron nitride is used for scooping.

[0024] Further preferably, the first solid state stirring has a rotation speed of 450 to 600 r / min and a time of 30 to 50 s;

[0025] The second stirring has a rotation speed of 750 to 850 r / min and a time of 165 to 185 s.

[0026] Preferably, in step (3), the preheating is specifically: placing a box-type resistance furnace at 430-470°C for preheating for 1.5-2.5h, wherein the heating rate during the preheating process is 0.5-1.0°C / s.

[0027] Preferably, in step (3), the extrusion deformation temperature during the extrusion process is 400-470° C., the extrusion ratio is 8-16:1, the extrusion rate is 4-6 mm / s, and the billet insulation time is 1.5-2.5 h.

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention discloses a high-strength and heat-resistant magnesium alloy containing Sn, which includes 6.3-9.7% Y, 1.5-2.7% Zn, less than or equal to 2.3% Sn, 0.3-0.7% Mn, less than or equal to 0.02% inevitable impurities, and the rest is Mg, in terms of weight percentage. The present invention successfully prepares a magnesium alloy with excellent high-temperature mechanical properties by constructing multi-scale heat-resistant phases and grain boundary segregation in the magnesium alloy. The alloy rare earth elements in the magnesium alloy of the present invention do not exceed 10%, which controls the cost while ensuring the advantage of lightweight magnesium alloy; the magnesium alloy of the present invention has a tensile strength of not less than 360MPa when the ambient temperature increases from 250°C to 300°C, and the tensile strength does not decrease with the increase of the ambient temperature, which is ahead of most of the current high-strength and heat-resistant magnesium alloys.

[0030] 2. The present invention also provides a method for preparing a Sn-containing high-strength heat-resistant magnesium alloy, which mainly comprises placing pure Mg, Mg-30Y master alloy, Mg-4.1Mn master alloy, pure Zn particles, and pure Sn particles in a preheated high-frequency induction melting furnace, melting them in sequence, stirring and ultrasonicating them to obtain a magnesium alloy ingot, homogenizing them to obtain a homogenized magnesium alloy billet, and then extruding them. The preparation method of the present invention has a simple process, is easy to replicate, easy to operate, and convenient for industrial application; in addition, the resistance furnace, hot press, etc. used in the preparation method of the present invention are all commonly used equipment in the field of magnesium alloy preparation technology, and have the characteristics of strong portability and easy industrial application. In addition, the Sn-containing high-strength heat-resistant magnesium alloy prepared by the preparation method of the present invention has the following characteristics: (1) the total rare earth content is not higher than 10%; (2) the intermediate phase precipitated inside includes micron-sized block LPSO and lamellar LPSO as well as Sn3Y5 phase, Mg-Y phase and nano-sized Mg-Zn phase and α-Mn; (3) the tensile strength of the magnesium alloy at room temperature is not less than 360 MPa and the elongation is greater than or equal to 7%; the tensile strength at 250°C and 300°C is not less than 320 MPa and the elongation is greater than or equal to 10%; (4) when the ambient temperature increases from 250°C to 300°C, the tensile strength is not less than 360 MPa, and the tensile strength does not decrease with the increase of the ambient temperature.

[0031] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0033] Figure 1 : are stress-strain curves of the magnesium alloys prepared in Examples 1 to 3 and Comparative Example 1 at room temperature;

[0034] Figure 2 : is the stress-strain curve of the magnesium alloy prepared in Examples 1 to 3 and Comparative Example 1 at 250°C;

[0035] Figure 3 : is the stress-strain curve of the magnesium alloy prepared in Examples 1 to 3 and Comparative Example 1 at 300°C;

[0036] Figure 4 In the figure, a, b and c are respectively the optical microscopic organization morphology image, the scanning electron microscopic organization morphology image, and the enlarged image of the blue box in b, of the magnesium alloy prepared in comparative example 1; d, e and f are respectively the optical microscopic organization morphology image, the scanning electron microscopic organization morphology image, and the enlarged image of the blue box in e, g, h and i are respectively the optical microscopic organization morphology image, the scanning electron microscopic organization morphology image, and the enlarged image of the blue box in h, and j, k and l are respectively the optical microscopic organization morphology image, the scanning electron microscopic organization morphology image, and the enlarged image of the blue box in k, of the magnesium alloy prepared in example 3. DETAILED DESCRIPTION

[0037] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0038] Example 1

[0039] A high-strength heat-resistant magnesium alloy containing Sn, wherein the composition of the magnesium alloy is, by weight percentage, 8.22% Y, 2.12% Zn, 0.48% Sn, 0.46% Mn, less than or equal to 0.02wt.% of inevitable impurities (the inevitable impurities are Fe, Si, etc.), and the rest is Mg. During the preparation process, the heating rate of the resistance furnace is adjusted to 0.5-1.0°C / s. The specific method comprises the following steps:

[0040] 1. Preparation of magnesium alloy ingots:

[0041] (1) placing a clean stainless steel crucible in a high-frequency induction melting furnace and preheating the furnace to 460° C. for 30 min, the preheating temperature is , and simultaneously introducing a mixed protective gas of CO2 and SF6 with a volume percentage of 99:1;

[0042] (2) The high-frequency induction melting furnace is heated to 720°C. After reaching the set temperature, the power is turned off and the weighed pure Mg is placed in the crucible. After it is fully melted, it is kept warm and allowed to stand for 30 minutes. The power is turned off and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0043] (3) After the high-frequency induction melting furnace is heated to 720°C, Mg-30Y master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0044] (4) After the high-frequency induction melting furnace is heated to 720° C., Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0045] (5) When the high-frequency induction melting furnace is heated to 720°C, pure Zn particles are added, and after the Zn particles are melted, the melt is stirred up and down with a colander coated with boron nitride for 5 minutes, and then the scum on the surface of the melt is removed;

[0046] (6) When the temperature is raised to 720°C, pure Sn particles are added. After the Sn particles are melted, the melt is stirred up and down with a colander coated with boron nitride for 5 minutes and then the scum on the surface of the melt is removed;

[0047] (7) After the impurities in the alloy melt are salvaged, the temperature is lowered to 640°C, and the stirring head is inserted into the bottom of the melt to perform the first semi-solid stirring at a speed of 450 r / min for 40 seconds. After the first stirring is completed, the speed is increased to 750 r / min, and the stirring head is placed in the middle of the liquid surface for a second stirring for 180 seconds;

[0048] (8) After the two-step stirring is completed, the melt is further heated to 680 °C and subjected to ultrasonic treatment at a power of 1800 W for 220 s. The crucible is then removed and rapidly water-cooled to obtain an ingot.

[0049] 2. Performing homogenization treatment on the magnesium alloy ingot: In order to eliminate the casting defects caused by smelting, the magnesium alloy ingot prepared above is subjected to homogenization treatment (first, after heating the temperature in a box-type heat treatment furnace to 510°C, the magnesium alloy ingot prepared above is placed in a resistance furnace for 16 hours and then air-cooled to room temperature) to obtain a homogenized magnesium alloy billet.

[0050] 3. Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: Cut a billet of appropriate size from the homogenized magnesium alloy billet prepared above, grind the surface oxide layer, put it into a 430°C resistance furnace together with the extrusion die for preheating for 2.5 hours, and extrude it in a horizontal extruder (the extrusion deformation temperature is 470°C, the extrusion ratio is 16:1, the extrusion rate is 6 mm / s, and the billet insulation time is 2.5 hours) to obtain a Sn-containing high-strength and heat-resistant magnesium alloy rod.

[0051] Example 2

[0052] A high-strength heat-resistant magnesium alloy containing Sn, wherein the composition of the magnesium alloy is, by weight percentage, 8.45% Y, 2.25% Zn, 0.95% Sn, 0.49% Mn, less than or equal to 0.02wt.% of inevitable impurities (the inevitable impurities are Fe, Si, etc.), and the rest is Mg. During the preparation process, the heating rate of the resistance furnace is adjusted to 0.5-1.0°C / s. The specific method comprises the following steps:

[0053] 1. Preparation of magnesium alloy ingots:

[0054] (1) placing a clean stainless steel crucible in a high-frequency induction melting furnace and preheating the furnace to 500° C. for 25 min, the preheating temperature is , and simultaneously introducing a mixed protective gas of CO2 and SF6 with a volume percentage of 99:1;

[0055] (2) The high-frequency induction melting furnace was heated to 740°C. After reaching the set temperature, the power was turned off and the weighed pure Mg was placed in the crucible. After it was fully melted, it was kept warm and allowed to stand for 30 minutes. The power was turned off and the slag on the surface of the melt was removed using a colander coated with boron nitride;

[0056] (3) After the high-frequency induction melting furnace is heated to 740°C, Mg-30Y master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0057] (4) After the high-frequency induction melting furnace is heated to 740°C, Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0058] (5) When the high-frequency induction melting furnace is heated to 740°C, pure Zn particles are added. After the Zn particles are melted, the melt is stirred up and down for 5 to 8 minutes with a colander coated with boron nitride, and then the slag on the surface of the melt is removed;

[0059] (6) When the high-frequency induction melting furnace is heated to 740°C, pure Sn particles are added. After the Sn particles are melted, the melt is stirred up and down with a colander coated with boron nitride for 7 minutes and then the slag on the surface of the melt is removed;

[0060] (7) After the impurities in the alloy melt are salvaged, the temperature is lowered to 650°C, and the stirring head is inserted into the bottom of the melt for the first semi-solid stirring at a speed of 500 r / min for 40 seconds. After the first stirring is completed, the speed is increased to 800 r / min, and the stirring head is placed in the middle of the liquid surface for the second stirring for 180 seconds;

[0061] (8) After the two-step stirring is completed, the melt is further heated to 690 °C and subjected to ultrasonic treatment at a power of 1800 W for 300 s. The crucible is then removed and rapidly water-cooled to obtain an ingot.

[0062] 2. Performing homogenization treatment on the magnesium alloy ingot: In order to eliminate the casting defects caused by smelting, the magnesium alloy ingot prepared above is subjected to homogenization treatment (first, after heating the temperature in a box-type heat treatment furnace to 520°C, the magnesium alloy ingot prepared above is placed in a resistance furnace for 16 hours and then air-cooled to room temperature) to obtain a homogenized magnesium alloy billet.

[0063] 3. Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: Cut a billet of appropriate size from the homogenized magnesium alloy billet prepared above, grind the surface oxide layer, put it into a 470°C resistance furnace together with the extrusion die for preheating for 1.5 hours, and extrude it in a horizontal extruder (the extrusion deformation temperature is 440°C, the extrusion ratio is 12:1, the extrusion rate is 5 mm / s, and the billet insulation time is 12 hours) to obtain a Sn-containing high-strength and heat-resistant magnesium alloy rod.

[0064] Example 3

[0065] A high-strength heat-resistant magnesium alloy containing Sn, wherein the composition of the magnesium alloy is, by weight percentage, 7.93% Y, 2.05% Zn, 1.57% Sn, 0.52% Mn, less than or equal to 0.02wt.% of inevitable impurities (the inevitable impurities are Fe, Si, etc.), and the rest is Mg. During the preparation process, the heating rate of the resistance furnace is adjusted to 0.5-1.0°C / s. The specific method comprises the following steps:

[0066] 1. Preparation of magnesium alloy ingots:

[0067] (1) Place a clean stainless steel crucible in a high-frequency induction melting furnace and preheat it to 510° C. for 20 min. The preheating temperature is , and a mixed protective gas of CO2 and SF6 with a volume percentage of 99:1 is introduced;

[0068] (2) The high-frequency induction melting furnace is heated to 750°C. After reaching this set temperature, the power is turned off and the weighed pure Mg is placed in the crucible. After it is fully melted, it is kept warm and allowed to stand for 25 minutes. The power is turned off and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0069] (3) After the high-frequency induction melting furnace is heated to 750°C, Mg-30Y master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 25 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0070] (4) After the high-frequency induction melting furnace is heated to 750° C., Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 25 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0071] (5) When the high-frequency induction melting furnace is further heated to 750°C, pure Zn particles are added, and after the Zn particles are melted, the melt is stirred up and down for 6 minutes using a colander coated with boron nitride, and then the slag on the surface of the melt is removed;

[0072] (6) When the high-frequency induction melting furnace is heated to 750°C, pure Sn particles are added, and after the Sn particles are melted, the melt is stirred up and down for 6 minutes with a colander coated with boron nitride, and then the slag on the surface of the melt is removed;

[0073] (7) After the impurities in the alloy melt are salvaged, the temperature is lowered to about 660°C, and the stirring head is inserted into the bottom of the melt for the first semi-solid stirring at a speed of 600 r / min for 40 seconds. After the first stirring is completed, the speed is increased to 850 r / min, and the stirring head is placed in the middle of the liquid surface for the second stirring for 180 seconds;

[0074] (8) After the two-step stirring is completed, the melt is further heated to 690 °C and ultrasonically treated at a power of 1800 W for 220 s. The crucible is then removed and rapidly water-cooled to obtain an ingot.

[0075] 2. Performing homogenization treatment on the magnesium alloy ingot: In order to eliminate the casting defects caused by smelting, the magnesium alloy ingot prepared above is subjected to homogenization treatment (first, after heating the temperature in a box-type heat treatment furnace to 515°C, the magnesium alloy ingot prepared above is placed in a resistance furnace for 16 hours and then air-cooled to room temperature) to obtain a homogenized magnesium alloy billet.

[0076] 3. Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: Cut a billet of appropriate size from the homogenized magnesium alloy billet prepared above, grind the surface oxide layer, put it into a 450°C resistance furnace together with the extrusion die for preheating for 2 hours, and extrude it in a horizontal extruder (the extrusion deformation temperature is 450°C, the extrusion ratio is 10:1, the extrusion rate is 5 mm / s, and the billet insulation time is 2 hours) to obtain a Sn-containing high-strength and heat-resistant magnesium alloy rod.

[0077] Example 4

[0078] A high-strength heat-resistant magnesium alloy containing Sn, wherein the composition of the magnesium alloy is, by weight percentage, 6.3% Y, 1.5% Zn, 2.3% Sn, 0.3% Mn, less than or equal to 0.02wt.% of inevitable impurities (the inevitable impurities are Fe, Si, etc.), and the rest is Mg. During the preparation process, the heating rate of the resistance furnace is adjusted to 0.5-1.0°C / s. The specific method comprises the following steps:

[0079] 1. Preparation of magnesium alloy ingots:

[0080] (1) placing a clean stainless steel crucible in a high-frequency induction melting furnace and preheating the furnace to 500° C. for 25 min, the preheating temperature is , and simultaneously introducing a mixed protective gas of CO2 and SF6 with a volume percentage of 99:1;

[0081] (2) The high-frequency induction melting furnace was heated to 740°C. After reaching the set temperature, the power was turned off and the weighed pure Mg was placed in the crucible. After it was fully melted, it was kept warm and allowed to stand for 30 minutes. The power was turned off and the slag on the surface of the melt was removed using a colander coated with boron nitride;

[0082] (3) After the high-frequency induction melting furnace is heated to 740°C, Mg-30Y master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0083] (4) After the high-frequency induction melting furnace is heated to 740°C, Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0084] (5) When the high-frequency induction melting furnace is heated to 740°C, pure Zn particles are added. After the Zn particles are melted, the melt is stirred up and down for 5 minutes with a colander coated with boron nitride, and then the slag on the surface of the melt is removed;

[0085] (6) When the high-frequency induction melting furnace is heated to 740°C, pure Sn particles are added. After the Sn particles are melted, the melt is stirred up and down with a colander coated with boron nitride for 7 minutes and then the slag on the surface of the melt is removed;

[0086] (7) After the impurities in the alloy melt are salvaged, the temperature is lowered to 650°C, and the stirring head is inserted into the bottom of the melt for the first semi-solid stirring at a speed of 500 r / min for 30 seconds. After the first stirring is completed, the speed is increased to 800 r / min, and the stirring head is placed in the middle of the liquid surface for the second stirring for 165 seconds;

[0087] (8) After the two-step stirring is completed, the melt is further heated to 680 °C and subjected to ultrasonic treatment at a power of 1600 W for 280 s. The crucible is then removed and rapidly water-cooled to obtain an ingot.

[0088] 2. Performing homogenization treatment on the magnesium alloy ingot: In order to eliminate the casting defects caused by smelting, the magnesium alloy ingot prepared above is subjected to homogenization treatment (first, after heating the temperature in a box-type heat treatment furnace to 510°C, the magnesium alloy ingot prepared above is placed in a resistance furnace for 14 hours and then air-cooled to room temperature) to obtain a homogenized magnesium alloy billet.

[0089] 3. Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: Cut a billet of appropriate size from the homogenized magnesium alloy billet prepared above, grind the surface oxide layer, put it into a 430°C resistance furnace together with the extrusion die for preheating for 2.5 hours, and extrude it in a horizontal extruder (the extrusion deformation temperature is 400°C, the extrusion ratio is 8:1, the extrusion rate is 4 mm / s, and the billet insulation time is 1.5 hours) to obtain a Sn-containing high-strength and heat-resistant magnesium alloy rod.

[0090] Example 5

[0091] A high-strength heat-resistant magnesium alloy containing Sn, wherein the composition of the magnesium alloy is, by weight percentage, 9.7% Y, 2.7% Zn, 0.1% Sn, 0.7% Mn, less than or equal to 0.02wt.% of inevitable impurities (the inevitable impurities are Fe, Si, etc.), and the rest is Mg. During the preparation process, the heating rate of the resistance furnace is adjusted to 0.5-1.0°C / s. The specific method comprises the following steps:

[0092] 1. Preparation of magnesium alloy ingots:

[0093] (1) placing a clean stainless steel crucible in a high-frequency induction melting furnace and preheating the furnace to 500° C. for 25 min, the preheating temperature is , and simultaneously introducing a mixed protective gas of CO2 and SF6 with a volume percentage of 99:1;

[0094] (2) The high-frequency induction melting furnace was heated to 740°C. After reaching the set temperature, the power was turned off and the weighed pure Mg was placed in the crucible. After it was fully melted, it was kept warm and allowed to stand for 30 minutes. The power was turned off and the slag on the surface of the melt was removed using a colander coated with boron nitride;

[0095] (3) After the high-frequency induction melting furnace is heated to 740°C, Mg-30Y master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0096] (4) After the high-frequency induction melting furnace is heated to 740°C, Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0097] (5) When the high-frequency induction melting furnace is heated to 740°C, pure Zn particles are added. After the Zn particles are melted, the melt is stirred up and down for 8 minutes with a colander coated with boron nitride, and then the slag on the surface of the melt is removed;

[0098] (6) When the high-frequency induction melting furnace is heated to 740°C, pure Sn particles are added. After the Sn particles are melted, the melt is stirred up and down with a colander coated with boron nitride for 7 minutes and then the slag on the surface of the melt is removed;

[0099] (7) After the impurities in the alloy melt are salvaged, the temperature is lowered to 660°C, and the stirring head is inserted into the bottom of the melt for the first semi-solid stirring at a speed of 600 r / min for 50 s. After the first stirring is completed, the speed is increased to 850 r / min, and the stirring head is placed in the middle of the liquid surface for the second stirring for 165 s;

[0100] (8) After the two-step stirring is completed, the melt is further heated to 680 °C and subjected to ultrasonic treatment at a power of 1800 W for 220 s. The crucible is then removed and rapidly water-cooled to obtain an ingot.

[0101] 2. Performing homogenization treatment on the magnesium alloy ingot: In order to eliminate the casting defects caused by smelting, the magnesium alloy ingot prepared above is subjected to homogenization treatment (first, after heating the temperature in a box-type heat treatment furnace to 520°C, the magnesium alloy ingot prepared above is placed in a resistance furnace for 14 hours and then air-cooled to room temperature) to obtain a homogenized magnesium alloy billet.

[0102] 3. Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: Cut a billet of appropriate size from the homogenized magnesium alloy billet prepared above, grind the surface oxide layer, put it into a 470°C resistance furnace together with the extrusion die for preheating for 1.5 hours, and extrude it in a horizontal extruder (the extrusion deformation temperature is 470°C, the extrusion ratio is 16:1, the extrusion rate is 6 mm / s, and the billet insulation time is 2.5 hours) to obtain a Sn-containing high-strength and heat-resistant magnesium alloy rod.

[0103] Comparative Example 1

[0104] A high-strength heat-resistant magnesium alloy without Sn, wherein the composition of the magnesium alloy is, by weight percentage, 8.35% Y, 1.98% Zn, 0.54% Mn, less than or equal to 0.02wt.% of inevitable impurities (the inevitable impurities are Fe, Si, etc.), and the rest is Mg. During the preparation process, the heating rate of the resistance furnace is adjusted to 0.5-1.0°C / s. The specific preparation method comprises the following steps:

[0105] 1. Preparation of magnesium alloy ingots:

[0106] (1) placing a clean stainless steel crucible in a high-frequency induction melting furnace and preheating it to 480° C. for 25 min, while introducing a mixed protective gas of CO2 and SF6 with a volume percentage of 99:1;

[0107] (2) The high-frequency induction melting furnace is further heated to 740°C. After reaching the set temperature, the power is turned off and the weighed pure Mg is placed in the crucible. After it is fully melted, it is kept at the temperature for 30 minutes. The power is turned off and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0108] (3) After the high-frequency induction melting furnace is further heated to 740° C., the Mg-30Y master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature and allowed to stand for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0109] (4) After the high-frequency induction melting furnace is further heated to 740° C., the Mg-4.1Mn master alloy is added, and after the master alloy is completely melted, the master alloy is kept at the temperature and allowed to stand for 30 minutes, the power is turned off, and the slag on the surface of the melt is removed using a colander coated with boron nitride;

[0110] (5) When the high-frequency induction melting furnace is further heated to 740°C, pure Zn particles are added, and after the Zn particles are melted, the melt is stirred up and down with a colander coated with boron nitride for 5 to 8 minutes, and then the slag on the surface of the melt is removed;

[0111] (6) After the impurities in the alloy melt are salvaged and the temperature is reduced to about 650°C, a stirring head is inserted into the bottom of the melt to perform the first semi-solid stirring at a speed of 500 r / min for 40 seconds, and then the speed is increased to 800 r / min, and the second stirring is performed at the middle of the liquid surface for 180 seconds;

[0112] (7) After the two-step stirring is completed, the melt is further heated to 690°C and ultrasonically treated at a power of 1800 W for 260 s. The crucible is then taken out and rapidly water-cooled to obtain a magnesium alloy ingot.

[0113] 2. Performing homogenization treatment on the magnesium alloy ingot: In order to eliminate the casting defects caused by smelting, the magnesium alloy ingot prepared above is subjected to homogenization treatment (first, after heating the temperature in a box-type heat treatment furnace to 515°C, the magnesium alloy ingot prepared above is placed in a resistance furnace for 16 hours and then air-cooled to room temperature) to obtain a homogenized magnesium alloy billet.

[0114] 3. Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: Cut a billet of appropriate size from the homogenized magnesium alloy billet prepared above, grind the surface oxide layer, put it into a 450°C resistance furnace together with the extrusion die for preheating for 2 hours, and extrude it in a horizontal extruder (the extrusion deformation temperature is 400°C, the extrusion ratio is 8:1, the extrusion rate is 4 mm / s, and the billet insulation time is 1.5 h) to obtain a high-strength and heat-resistant magnesium alloy bar that does not contain Sn.

[0115] Performance Testing

[0116] 1. The room temperature mechanical properties of the Sn-containing high-strength and heat-resistant magnesium alloys prepared in Examples 1 to 5 and the Sn-free high-strength and heat-resistant magnesium alloy prepared in Comparative Example 1 were tested. The results are shown in Table 1.

[0117] Table 1 Room temperature mechanical properties of high strength and heat resistant magnesium alloys prepared in different embodiments and comparative example 1

[0118]

[0119]

[0120] As can be seen from Table 1, the magnesium alloy prepared by conventional extrusion deformation in the present invention has good high-temperature mechanical properties. In particular, Example 3 shows the best strength. At room temperature, the yield strength is not less than 330MPa and the ultimate tensile strength is not less than 390MPa. At the same time, it retains an elongation of 7.6%, which meets the needs of most application scenarios. At the same time, it should be noted that the magnesium alloy prepared in Example 3 still maintains a tensile strength of more than 360MPa when the ambient temperature increases from 250°C to 300°C, showing excellent high-temperature stability, ahead of most current high-strength and heat-resistant magnesium alloys, and suitable for the application of high-precision products.

[0121] Example 3 exhibits the best high-temperature mechanical properties, which is mainly due to the presence of multi-scale heat-resistant phases in the magnesium alloy prepared in Example 3, namely, micron-scale block and layered LPSO, Mg-Y, Sn3Y5, and nano-scale Mn. At the same time, certain stacking faults were observed inside the alloy. These stacking faults, as the predecessors of layered LPSO, can also play a certain role in hindering dislocations. The EDS surface scan results at the grain boundaries show that there is obvious segregation of Y, Zn, Sn, and Mn elements at the grain boundaries, which has a positive effect on the stability of the grain boundaries at high temperatures. During the high-temperature tensile process at 300°C, the magnesium alloy Dislocation, a lot of<c+a> Dislocations are also activated. However, due to the rapid increase in strain during the tensile process, the dislocation density near the fracture increases rapidly. The micron-sized bulk LPSO phase, Mg-Y phase, and Sn3Y5 phase can significantly hinder the movement of basal and non-basal dislocations, forcing the dislocations to bypass the second phase to move. The nano-sized Mn and some stacking faults can act as an effective barrier to cause dislocations to move after cutting. Obviously, the multi-scale heat-resistant phase with good thermal stability hinders the movement of dislocations at high temperatures and pins the grain boundaries to grow. In addition, Y, Zn, Sn, and Mn atoms will produce obvious segregation at the grain boundaries. The atomic radius difference between solute atoms and Mg atoms will produce lattice distortion and hinder dislocation movement. Secondly, the elastic interaction between solute atoms and dislocations will produce Cottrell gas clusters, which further increase the resistance to dislocation movement. In addition, the segregation of solute atoms at grain boundaries will reduce the energy of the grain boundaries and inhibit the coarsening of grains during high-temperature thermal exposure. Therefore, the grain boundary segregation of solute atoms gives the Example 3 alloy good grain size stability, which is a key factor in the excellent high temperature strength of the alloy.

[0122] Figure 1 : are stress-strain curves of the magnesium alloys prepared in Examples 1 to 3 and Comparative Example 1 at room temperature; Figure 2 : is the stress-strain curve of the magnesium alloy prepared in Examples 1 to 3 and Comparative Example 1 at 250°C; Figure 3 The stress-strain curves of the magnesium alloys prepared in Examples 1 to 3 and Comparative Example 1 at 300°C are shown. It can be seen that the change in Sn content will greatly affect the room temperature and high temperature strength of the alloy. Example 2 obtains the best room temperature and high temperature strength, and the tensile strength at 250°C and 300°C is almost unchanged. Figure 4 a, b and c are respectively the optical microscopic microstructure morphology, scanning electron microscopic microstructure morphology, and the enlarged image of the blue frame in b of the magnesium alloy prepared in comparative example 1, d, e and f are respectively the optical microscopic microstructure morphology, scanning electron microscopic microstructure morphology, and the enlarged image of the blue frame in e of the magnesium alloy prepared in example 1, g, h and i are respectively the optical microscopic microstructure morphology, scanning electron microscopic microstructure morphology, and the enlarged image of the blue frame in h of the magnesium alloy prepared in example 2, j, k and l are respectively the optical microscopic microstructure morphology, scanning electron microscopic microstructure morphology, and the enlarged image of the blue frame in k of the magnesium alloy prepared in example 3. Figure 4It can be seen that the magnesium alloys prepared in Examples 1 to 3 have almost complete dynamic recrystallization microstructures, while the magnesium alloy prepared in Example 3 exhibits an obvious bimodal microstructure, which is mainly composed of a large number of lamellar and blocky long-period stacked ordered phases in the coarse-grained non-recrystallized region. For the other three alloys, the lamellar LPSO phase is almost completely broken and distributed in small grains.

[0123] The present invention transforms the Mg-Y phase with poor thermal stability in the rare earth magnesium alloy into the Sn3Y5 phase with higher thermal stability by alloying with Sn. A magnesium alloy with excellent high temperature mechanical properties is prepared, and the rare earth element of the prepared alloy does not exceed 10%. While controlling the cost, the advantage of lightweight magnesium alloy is also maintained. The multi-scale heat-resistant phase effectively hinders dislocation movement and pins grain boundary sliding during high temperature tensile processing. The preferred magnesium alloy has a tensile strength of not less than 360MPa at an ambient temperature of 250°C. At 250°C, the tensile strength is much higher than the related heat-resistant magnesium alloys reported in CN117778844A, CN118006989A, CN115161528B, etc. When the ambient temperature increases from 250°C to 300°C, the tensile strength of the preferred magnesium alloy does not decrease significantly, and its tensile strength maintains excellent high temperature stability, which is ahead of most of the currently reported high-strength heat-resistant magnesium alloys.

[0124] In summary, the present invention provides a high-strength and heat-resistant magnesium alloy containing Sn, and a high-strength and heat-resistant magnesium alloy containing Sn is obtained by constructing a multi-scale micron-scale and nano-scale second phase in the magnesium alloy and pinning the grain boundary movement. In the embodiment, the blocky LPSO phase inhibits the occurrence of dynamic recrystallization in the early stage of deformation, and after extrusion and crushing, the dynamic recrystallization can be promoted by the particle excitation induced nucleation mechanism. The addition of Sn introduces Sn3Y5 second phase strengthening on the one hand, and inhibits the second phase strengthening of the Mg-Y phase on the other hand. Preferably, the yield strength of Example 3 at room temperature is not less than 330MPa, the ultimate tensile strength is not less than 390MPa, and the elongation of 7.6% is retained, which meets most application scenarios. At the same time, the magnesium alloy prepared in Example 3 is increased from 250°C to 300°C, and the tensile strength is still maintained above 360MPa, showing excellent high temperature stability. The present invention also provides a method for preparing a low-cost, high-toughness, high-electromagnetic shielding magnesium alloy, which is simple in process, easy to replicate, easy to operate, and convenient for industrial application. In addition, the resistance furnace, hot press, rolling mill, etc. used in the present invention are all commonly used equipment in the field of magnesium alloy preparation technology, and have the characteristics of strong portability and easy industrial application.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A high-strength and heat-resistant magnesium alloy containing Sn, It is characterized in that In terms of weight percentage, the magnesium alloy includes 6.3-9.7% Y, 1.5-2.7% Zn, less than or equal to 2.3% Sn, 0.3-0.7% Mn, less than or equal to 0.02% inevitable impurities, and the rest is Mg.

2. The magnesium alloy according to claim 1, It is characterized in that The average grain size of the extruded magnesium alloy is no greater than 5 μm.

3. A method for preparing a magnesium alloy according to any one of claims 1 to 2, It is characterized in that The preparation method comprises the following steps: (1) Preparing a magnesium alloy ingot: placing pure Mg, Mg-30Y master alloy, Mg-4.1Mn master alloy, pure Zn particles, and pure Sn particles in a preheated high-frequency induction melting furnace for sequential melting, removing scum from the surface of the melt and cooling to 640-660°C, inserting a stirring head into the bottom of the melt and performing semi-solid stirring at a speed of 450-600 r / min for 30-50 s, increasing the speed to 750-850 r / min after the first stirring, and continuing to perform a second stirring at the middle of the liquid surface for 165-185 s, and after the two stirrings are completed, heating the stirred melt to 680-690°C, performing ultrasonic treatment at a power of 1600-1800 w for 220-280 s, and then removing the water cooling to obtain a magnesium alloy ingot; (2) homogenizing the magnesium alloy ingot: heating the box-type heat treatment furnace to 510-520° C., placing the magnesium alloy ingot in a resistance furnace for 14-18 hours, and then air-cooling it to room temperature to obtain a homogenized magnesium alloy billet; (3) Preparation of Sn-containing high-strength and heat-resistant magnesium alloy: After the surface oxide layer of the homogenized magnesium alloy billet is polished, the billet is placed together with the extrusion die in a preheated box-type resistance furnace, and extruded in a horizontal extruder to obtain Sn-containing high-strength and heat-resistant magnesium alloy.

4. The preparation method according to claim 3, It is characterized in that In step (1), the preheating is specifically as follows: placing the cleaned stainless steel crucible in a high-frequency induction melting furnace and heating it to 460-510°C for 20-30 minutes, while introducing 99:1 volume percent CO 2 and SF 6 The mixed protective gas formed.

5. The preparation method according to claim 3, It is characterized in that In step (1), the specific method for preparing the magnesium alloy ingot is: A. Heat the high-frequency induction melting furnace to 720-750°C, add pure Mg to fully melt it, keep it warm and let it stand for 25-35 minutes to remove the slag on the surface of the melt; B. Continue to heat the high-frequency induction melting furnace to 720-750° C., add Mg-30Y master alloy, and keep the master alloy warm for 25-35 minutes after it is completely melted, and remove scum on the surface of the melt; C. Continue to heat the high-frequency induction melting furnace to 720-750° C., add Mg-4.1Mn master alloy, and keep the master alloy warm for 25-35 minutes after it is completely melted, and remove scum on the surface of the melt; D. When the high-frequency induction melting furnace is further heated to 720-750° C., pure Zn particles are added to melt the melt and scum is removed from the surface of the melt; E. When the high-frequency induction melting furnace is further heated to 720-750° C., pure Sn particles are added to melt the melt, and the scum on the surface of the Sn melt is removed after stirring the melt for 5-8 minutes; F. After the impurities in the alloy melt are salvaged and the temperature is reduced to 640-660°C, use the stirring head to extend into the bottom of the melt for the first solid-state stirring, and then place the stirring head in the middle of the liquid surface for the second stirring; G. After the two stirrings are completed, the stirred melt is heated to 680-690°C, ultrasonically treated at a power of 1600-1800W for 220-280s, and then the water cooling is removed to obtain a magnesium alloy ingot.

6. The preparation method according to claim 5, It is characterized in that In the process of removing scum on the surface of the melt, a colander coated with boron nitride is used for scooping.

7. The preparation method according to claim 5, It is characterized in that The first solid state stirring has a rotation speed of 450 to 600 r / min and a time of 30 to 50 s; The second stirring has a rotation speed of 750 to 850 r / min and a time of 165 to 185 s.

8. The preparation method according to claim 3, It is characterized in that In step (3), the preheating is specifically as follows: placing a box-type resistance furnace at 430-470°C for preheating for 1.5-2.5 hours, wherein the heating rate during the preheating process is 0.5-1.0°C / s.

9. The preparation method according to claim 3, It is characterized in that In step (3), during the extrusion process, the extrusion deformation temperature is 400-470° C., the extrusion ratio is 8-16:1, the extrusion rate is 4-6 mm / s, and the billet insulation time is 1.5-2.5 h.